Functional interplay of DnaE polymerase, DnaG primase and DnaC helicase within a ternary complex, and primase to polymerase hand-off during lagging strand DNA replication in Bacillus subtilis - Rannou, Olivier; Le Chatelier, Emanuelle; Larson, Marilynn A.; Nouri, Hamid; Dalmais, Bérengère; Laughton, Charles; Laurent, Jannière; Soultanas, Panos (Oxford Journals, 2013)
Bacillus subtilis has two replicative DNA polymerases. PolC is a processive high-fidelity replicative polymerase, while the error-prone DnaEBs extends RNA primers before hand-off to PolC at the lagging strand. We show that DnaEBs interacts with the replicative helicase DnaC and primase DnaG in a ternary complex. We characterize their activities and analyse the functional significance of their interactions using primase, helicase and primer extension assays, and a ‘stripped down’ reconstituted coupled assay to investigate the coordinated displacement of the parental duplex DNA at a replication fork, synthesis of RNA primers along the lagging strand and hand-off to DnaEBs. The DnaG– DnaEBs hand-off takes place after de novo polymerization of only two ribonucleotides by DnaG, and does not require other replication proteins. Furthermore, the fidelity of DnaEBs is improved by DnaC and DnaG, likely via allosteric effects induced by direct protein–protein interactions that lower the efficiency of nucleotide mis-incorporations and/or the efficiency of extension of mis-aligned primers in the catalytic site of DnaEBs. We conclude that de novo RNA primer synthesis by DnaG and initial primer extension by DnaEBs are carried out by a lagging strand–specific subcomplex comprising DnaG, DnaEBs and DnaC, which stimulates chromosomal replication with enhanced fidelity.